Assessing the effect of night ventilation on PCM performance in high-rise residential buildings. (November 2019) - Soudian, Shahrzad; Berardi, Umberto
This article investigates the possibility to enhance the use of latent heat thermal energy storage (LHTES) as an energy retrofit measure by night ventilation strategies. For this scope, phase change materials (PCMs) are integrated into wall and ceiling surfaces of high-rise residential buildings with highly glazed facades that experience high indoor diurnal temperatures. In particular, this article investigates the effect of night ventilation on the performance of the PCMs, namely, the daily discharge of the thermal energy stored by PCMs. Following previous experimental tests that have shown the efficacy of LHTES in temperate climates, a system comprising two PCM layers with melting temperatures selected for a year-around LHTES was considered. To quantify the effectiveness of different night ventilation strategies to enhance the potential of this composite PCM system, simulations in EnergyPlus TM were performed. The ventilation flow rate, set point temperature, and operation period were the main tested parameters. The performance of the PCMs in relation to the variables was evaluated based on indoor operative temperature and cooling energy use variations in Toronto and New York in the summer. The solidification of the PCMs was analyzed based on the amount of night ventilation needed in each climate condition. The results quantify the positive impact of combining PCMs with night ventilation on cooling energy reductions and operative temperature regulation of the following days. In particular, the results indicate higher benefits obtainable with PCMs coupled with night ventilation in the context of Toronto, since this city experiences higher daily temperature fluctuations. The impact of night ventilation design variables on the solidification rate of the PCMs varied based on each parameter leading to different compromises based on the PCM and climate characteristics.